CONSTRUCTION AND VALIDATION OF EDUCATIONAL HEALTHCARE GAMES: AN INTEGRATIVE REVIEW STUDY (Interdisciplinary Studies Journal, 2025)
The health promotion proposal emphasizes the importance of education, going beyond the mere transmission of knowledge, seeking comprehensive health. The use of games emerges as a tool to transform the educational approach in health promotion, as the playful element generates effective learning and the transfer of knowledge to reality. This review study addresses the development and validation of board and card games as resources for health promotion. The guiding questions of the research include the steps for creating and validating educational games in the health field, the types of games developed, and the target audience. The research highlights the relevance of these studies, especially in the current scenario, emphasizing the importance of using board and card games as tools for health and educational promotion. Therefore, the research underscores the importance of games as an effective and comprehensive approach to health promotion, involving well-being.
Keywords: Games; Validation; Health Promotion